Tertiary Lymphoid Structures, Immune Response, and Prognostic Relevance in Non-Small Cell Lung Cancer. (2nd January 2023) - Giatromanolaki, Alexandra; Chatzipantelis, Paschalis; Contrafouris, Constantinos A.; Koukourakis, Michael I.
Abstract: We assessed the presence of 'tertiary lymphoid structures' (TLS) in a series of surgically treated non-small cell lung carcinomas (NSCLC). The TLS-density in the tumor periphery (pTLS) ranged from 0 to 1.8 (median 0.45), while in inner tumor areas (iTLS) ranged from 0 to 1.0 (median 0); ( p  < 0.0001). High pTLS-density was linked with early stage of the disease. Glycolysis-related enzyme expression (MCT1, Hexokinase 2) was linked with high pTLS-density ( p  < 0.05). High pTLS and iTLS densities were linked with better postoperative prognosis ( p  = 0.02 and p  = 0.01, respectively). Assessment of TLS is a useful prognostic marker in NSCLC.